2011
DOI: 10.1097/sle.0b013e31822d02dc
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Gastrectomy With D2 Lymph Node Dissection for Gastric Cancer

Abstract: The results of this meta-analysis suggest that LGD2 results in less blood loss and postoperative complications and also less pain and faster bowel function recovery, with similar harvested lymph nodes and overall survival rate comparing to OGD2. However, we also see the need for further high-quality randomized controlled trials comparing the 2 procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 25 publications
3
40
1
1
Order By: Relevance
“…In our experience, even serosa-positive cancer (T4a) patients treated using MIS experienced similar survival and recurrence outcomes, compared to open surgery 15. The results of a meta-analysis demonstrated that compared with open surgery, laparoscopic gastrectomy with D2 LN dissection had similar overall survival rates, comparable numbers of retrieved LNs, less blood loss, less pain, reduced postoperative complications, and shorter hospital stays 41. However, the reduced postoperative complication rate resulted from a decreased incidence of minor complications (e.g., wound infections and postoperative ileus), but the incidence of major complications was similar to open surgery 41.…”
Section: Mis For Agcmentioning
confidence: 73%
See 1 more Smart Citation
“…In our experience, even serosa-positive cancer (T4a) patients treated using MIS experienced similar survival and recurrence outcomes, compared to open surgery 15. The results of a meta-analysis demonstrated that compared with open surgery, laparoscopic gastrectomy with D2 LN dissection had similar overall survival rates, comparable numbers of retrieved LNs, less blood loss, less pain, reduced postoperative complications, and shorter hospital stays 41. However, the reduced postoperative complication rate resulted from a decreased incidence of minor complications (e.g., wound infections and postoperative ileus), but the incidence of major complications was similar to open surgery 41.…”
Section: Mis For Agcmentioning
confidence: 73%
“…The results of a meta-analysis demonstrated that compared with open surgery, laparoscopic gastrectomy with D2 LN dissection had similar overall survival rates, comparable numbers of retrieved LNs, less blood loss, less pain, reduced postoperative complications, and shorter hospital stays 41. However, the reduced postoperative complication rate resulted from a decreased incidence of minor complications (e.g., wound infections and postoperative ileus), but the incidence of major complications was similar to open surgery 41. Recently, large-scale multicenter RCTs began enrollment of patients to assess the feasibility of MIS for AGC in Korea, Japan, and China (Table 2).…”
Section: Mis For Agcmentioning
confidence: 99%
“…Opponents of this technique question the oncological quality of the procedure compared to the classical approach. Comparison of laparoscopic and classical methods concluded that the number of lymph nodes removed during the operation is similar regardless of preferred technique [9–11]. Histopathological evaluation in all abovementioned operations proved them to be radical, and lymphangiectomy included lymph nodes from the D2 group.…”
Section: Discussionmentioning
confidence: 99%
“…Majority of them reported that LS was associated with less blood loss, faster recovery of patients, less pain, shorter hospital stay as well as longer operation time (12)(13)(14)(15)(16). Some meta-analysis also demonstrated similar results (17). In terms of long-term outcomes of prospective randomized studies, only that of small samplesized studies is available.…”
Section: Previous Studies and Current Ongoing Multiinstitutional Largmentioning
confidence: 94%